(63+19)-a=47; (92-43)+a=63 ; a-(28+19)=15; a-(42-28)=45
Răspunsuri la întrebare
Răspuns de
4
(63+19)-a=47
82-a=47
-a=47-82
-a=-35 /•(-1)
a=35
(92-43)+a=63
49+a=63
a=63-49
a=14
a-(28+19)=15
a-47=15
a=15+47
a=62
a-(42-28)=45
a-14=45
a=45+14
a=59
82-a=47
-a=47-82
-a=-35 /•(-1)
a=35
(92-43)+a=63
49+a=63
a=63-49
a=14
a-(28+19)=15
a-47=15
a=15+47
a=62
a-(42-28)=45
a-14=45
a=45+14
a=59
Alte întrebări interesante
Matematică,
8 ani în urmă
Fizică,
8 ani în urmă
Informatică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Biologie,
9 ani în urmă